Recursos lúdicos manipulativos y relaciones lógico-matemáticas en niños de nivel inicial II de la Escuela de Educación Básica Alonso de Mercadillo de la ciudad de Loja, periodo 2022-2023 - Cueva Suarez, Nattaly Jazbeth (2024)
Thought processes construct logical-mathematical relations, fostering understanding through analysis, comparison, abstraction, and imagination. These processes are crucial for the development of cognitive skills in children, promoting interest and motivation in the mathematical domain. The objective of the present study was to determine how manipulative ludic resources improve the development of logical-mathematical relations in children of initial level II at the Escuela Educación Básica Alonso de Mercadillo in the city of Loja. The quasi-experimental research was conducted using a mixed methods approach with inductive and deductive methodologies. Data were collected using the EVAMAT-0 test administered to a sample of twenty-five children. The results revealed that 64% of the participants presented low levels of logical-mathematical reasoning. In response, manipulative ludic resources were implemented in the intervention activities. Post-test results indicated significant improvement, with 60% of children demonstrating high levels of mathematical ability. This showed the effectiveness of manipulative ludic resources in fostering mathematical development through practical learning, experimentation, gand discovery. Improvements were observed in quantity and counting, figure recognition, number-quantity relationships, and solving simple problems. Keywords: notions, memory, exploration, experimentation, manipulative material, mathematics.